Desarrollo de conceptos básicos de probabilidad en un aula compartida por estudiantes sordos y oyentes de grado séptimo (2020)
This paper presents the design and implementation of a didactic sequence to develop the concepts of probability in 7th grade students of a classroom shared between deaf and hearing children, and which has the support of a Colombian Sign Language Interpreter (LSC). For its design, the concept of visual learning, the use of concrete material, graphic representations, experimentation and recreational activities is privileged, in order to overcome communication barriers and encourage students to build the basic concepts of probability, such as: random experiment, sample space, tree diagram, probability assignment using the classical approach and basic axioms; which correspond to the basic competence standards defined by the Ministry of National Education for seventh grade students. Initially a diagnostic test is carried out that indicates that neither deaf nor hearing students have any notion of probability. Subsequently, the execution and results obtained from each of the activities of the sequence between both populations are compared: deaf and hearing. The results obtained when applying and evaluating the didactic sequence show that deaf children assimilated the concepts in the same way as the listeners, needing a minimal intervention from the LSC interpreter for the understanding and development of the activities.